Making palaeoclimatology research policy‐relevant: Insights and experience from the DECADAL Project - Celia Martin‐Puertas; Laura Boyall; Alice M. Milner; Ashley M. Abrook; Amen Al‐Yaari; Alice Carter‐Champion; Daisy Fallows; Katy Flowers; Paul Lincoln; Simon Blockley; Achim Brauer; Armand Hernandez; et al. (Journal of Quaternary Science, 2026)
Quaternary palaeoclimatology uniquely provides insights and new evidence about climate variability trends and extremes prior to the instrumental record; yet, its knowledge is rarely integrated into governmental decision‐making. This opinion piece shares lessons and experience from the UKRI‐funded DECADAL project, which bridges palaeoclimate science and policy through co‐production with UK climate services and policy institutions. The views expressed represent a joint perspective of the academic and non‐academic actors involved in the project, highlighting the challenges that we faced and the solutions that we adopted. We found that an iterative collaboration through aligning research questions, outputs and formats with user needs builds trust, increases relevance and creates pathways for long‐term policy uptake. DECADAL demonstrates that engaging with relevant policy and other end‐user groups does not compromise scientific excellence; rather, it drives methodological innovation and rigour, fosters creativity and produces high‐impact, original publications that also have relevance beyond an academic audience. We argue that embedding policy engagement should be viewed as a collective community endeavour rather than the effort of an individual or research team. By embracing co‐production, palaeo‐scientists can strengthen the societal value of their research, open new avenues for innovation and collaboration, and collectively shape climate‐informed decision‐making.